In pursuit of more fruitful food systems - Sulser, Timothy B.; Wiebe, Keith D.; Gustafson, David; Asseng, Senthold; Fraisse, Clyde; Guan, Kaiyu (Springer, 2022)
Recent analyses suggest that global fruit and vegetable (F&V) production will need to increase by 50–150% by 2050 to achieve sustainable and healthy diets for all 10 billion people expected to inhabit the world (Stratton et al. 2021). Meeting this increased demand will be very difficult due to numerous factors, including the scarcity of labor, dwindling water supplies for irrigation, and climate change. We have just completed a 5-year project (Agriculture and Food Systems Institute 2022) that began to tackle this daunting challenge: fruit and vegetable supply chains: climate adaptation and mitigation opportunities. We identified and tested climate adaptation and mitigation strategies in these supply chains through the development and application of a novel integrated methodology that included climate, crop, economic, and life cycle assessment (LCA) models, following protocols developed by the Agricultural Model Intercomparison and Improvement Project (AgMIP) (https://agmip.org/). Consistent with AgMIP standards, our modeling tools are for open use and are broadly applicable to other crops and regions, subject to normal input data requirements.